New, simple and express determination of lamotrigine in tablets by using diazole red 2J - Miedviedieva, K. P.; Vasyuk, S. O.; Korzhova, A. S.; Pavljuk, I.; Мєдвєдєва, Катерина Павлівна; Васюк, Світлана Олександрівна; Коржова, Алла Станіславівна (My University, 2022)
Epilepsy is considered one of the most common chronic neurological diseases among humans. Lamotrigine is an effec-tive new-generation anticonvulsant, which is widely introduced to the pharmaceutical market by various drug manufac-turers. That is why the urgent aim for pharmaceutical analysis is developing of high precision, valid, accessible and quantitative methods for lamotrigine in pharmaceuticals. The aim of the work is to study the optimal conditions for the reaction between lamotrigine and diazole red 2J, to de-fine the coefficients of stoichiometric relationships in the “pharmaceutical substance – reagent” system and to develop a valid, sensitive and easy-to-follow technique for the quantitative determination of lamotrigine in pharmaceutical forms. Material and methods. As reagent and solvent, diazole red 2J of AR grade and acetone of AR grade were used. Analyt-ical equipment: Specord 200 spectrophotometer, ABT-120-5DM electronic scales, Elmasonic E 60H ultrasonic bath and measuring glassware of A class. Results. A new spectrophotometric method for the quantitative determination of lamotrigine in four pharmaceutical formulations based on interaction with diazole red 2J in acetone medium has been developed. The proposed method is valid according to such validation characteristics as linearity, precision, intra-laboratory precision, accuracy, applica-tion range and robustness. The subordination to Behr's law is in the range of concentrations of 2.20–3.36 mg/100 ml. The LOD and LOQ values based on the values of the calibration line were 0.00450 % and 0.0138 % respectively. It was found that the studied coloured solutions are stable for at least 60 min and fluctuations in the amount of added red diazole 2J solution within ±10 % do not significantly affect the value of optical density. The coefficients of stoichio-metric ratios between the components of the “lamotrigine – diazole red 2J” reaction mixture were defined by three methods and are 1:1. The predicted complete uncertainty of the results of analysis for quantitative determination of lamotrigine in the pharmaceutical form (2.2 %) does not exceed the maximum allowable uncertainty for the technique (3.2 %) and meets the SPhU requirements. Conclusions. According to the experimental data, the technique can be correctly reproduced and it is suitable for using in laboratories of the State Inspection for Quality Control of Medicines and QCD of the chemicopharmaceutical enterprises
Keywords: spectrophotometry; analysis; lamotrigine; diazole red 2J; validation studies; Ukrainian Pharmacopeia